Triterpenes in breast cancer: a systematic review of preclinical evidence in rodents - Prodea, Alexandra; Munteanu, Andreea; Jorgovan, Mihaela; Batrina, Oana; Mioc, Marius; Soica, Irina; Trandafirescu, Cristina; Soica, Codruta (Frontiers in Pharmacology, 2025)
IntroductionBreast cancer poses a significant health problem for women worldwide due to late-stage diagnosis, toxicity of standard therapy and drug resistance. Several therapeutic alternatives, including triterpenes, show promising therapeutic potential and reduced toxicity in vitro and in vivo models.MethodologyWe aimed to systematically review the data provided by rodent models of breast cancer regarding the anticancer effect, mechanisms of action and safety of triterpenes to assess if clinical translation to human studies is supported by current evidence. After a two-phase screening process, our search of PubMed/Medline, Web of Science (WOS) and Scopus databases yielded 163 articles that were included in the analysis.Results and discussionsTriterpenes were used in free form, semisynthetic derivatives (triterpenoids), cotreatment with other drugs or formulated as liposomes, micelles and nanoparticles (NPs). The vote-counting analysis showed a superior effect of triterpenes compared to controls in terms of tumor volume and weight reduction, findings also confirmed by a sensitivity analysis. We also searched for possible sources of heterogeneity in the studies assessed by analyzing several subgroups, which provided valuable information. They exerted their effect through various mechanisms such as apoptosis induction, metastasis and angiogenesis inhibition and decreased several cancer biomarkers such as ki-67, proliferating cell nuclear antigen (PCNA) and matrix metalloproteinases (MMP). The toxicity assessment revealed that triterpenes have in general, insignificant or absent toxicity, with only a small number of studies reporting serious side effects such as leukopenia, hepatotoxicity and mortality at specific doses that were reversed in some cases by the use of carriers, which hold the potential to enhance the therapeutic effect of triterpenes while reducing their systemic toxicity.ConclusionWe concluded that the current in vivo evidence does not support the clinical translation of triterpenes for the treatment of breast cancer due to methodological and clinical heterogeneity as well as the lack of toxicity data in a significant number of studies. Nonetheless, this field holds great potential for clinical translation, which could be attained through more rigorous methodologies and the collection of comprehensive experimental data.